Spectroscopic line parameters of 12CH4 for atmospheric composition retrievals in the 4300–4500 cm−1 region. (January 2017) - Hashemi, R.; Predoi-Cross, A.; Nikitin, A.V.; Tyuterev, Vl.G.; Sung, K.; Smith, M.A.H.; Malathy Devi, V.
Abstract: Due to the importance of methane as a trace atmospheric gas and a greenhouse gas, we have carried out a precise line-shape study to obtain the CH4 –CH4 and CH4 –air half-width coefficients, CH4 –CH4 and CH4 –air shift coefficients and off-diagonal relaxation matrix element coefficients for methane transitions in the spectral range known as the " methane Octad ". In addition, the associated temperature dependences of these coefficients have been measured in the 4300–4500 cm −1 region of the Octad. The high signal to noise ratio spectra of pure methane and of dilute mixtures of methane in dry air with high resolution have been recorded at temperatures from 148 K to room temperature using the Bruker IFS 125 HR Fourier transform spectrometer (FTS) at the Jet Propulsion Laboratory, Pasadena, California. The analysis of spectra was done using a multispectrum non-linear least-squares curve fitting technique. Theoretical calculations have been performed and the results are compared with the previously published line positions, intensities and with the line parameters available in the GEISA and HITRAN2012 databases. Abstract : Graphical abstract: Section of the spectra of pure methane and methane broadened by air in the spectral range of the υ 3 + υ 4 . The bottom panels show the fit residuals obtained using the Voigt and quadratic speed-dependent Voigt profiles including line mixing. Abstract : Highlights: Self- and air–half-width, pressure-shift, line mixing coefficients are reported. The temperature dependence of CH4 –CH4 and CH4 –air half-width, CH4 –CH4 and CH4 –air shift parameters in the υ 3 + υ 4 band of methane were presented. The temperature dependencies of self-, air-broadened line parameters are presented. The quadratic SDV profile including line mixing was used in the retrievals.